Formal models of language systems - Chetverikov; Fedorova, T.; Vechirskaya, I.; Четвериков, Г. Г.; Федорова, Т. М.; Вечірська, І. Д.; Вечирская, И. Д. (Харківський національний автомобільно-дорожній університет, 2011)
The basic construction concepts of unifying two-digit and multi-valued means of processing symbolic data are considered. The present approach is based upon a single methodological and special purpose principle by applying the proposed methods of the intelligence theory for mathematical input/output data and their intermediate transformations by an appropriate AFP-structure of the third grade.
Формальні моделі мовних систем
Формальные модели языковых систем
Keywords: multivalued intellectual system; language systems; parallelism (spatial); AFP (algebra of finite predicates); AFP-structures; knowledge base; multiplevalued logic; багатозначна інтелектуальна система; мовна система; паралелізм (просторовий); АСП (алгебра скінченних предикатів); АСП-структури; база знань; багатозначна логіка; многозначная интеллектуальная система; языковая система; параллелизм (пространственный); АКП (алгебра конечных предикатов); АКП-структуры; база знаний; многозначная логика; 519.7:007.52; 519.711.3